Fenomena Kekerasan Sosial dan Struktur Majemuk Masyarakat Indonesia - Yayan Rudianto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2012)
Reformation of Republic Indonesia Authority as unitary state that has been held since 1998 places the government not in a good position in the eye of its people. The gap between the great expectation on the reformation and the reality of having a happier life that have not felt by the people, creates frustration, that one of the forms is expressed by social violence act. According to KontraS, along 2011, social violence happened in Indonesia, based on intensity and escalation: there are more or less 10 cases happened between April and July 2011 and September - December 2011. These violence generally relates to the conflict of natural resource management, local politic succession, until social friction of society daily life. The pattern of the violence involves society community, police, and business corporation community in the location of the event. Besides Lampung, Bima, and Papua, the violence spot also happens in Bali and Ambon. In order not to threaten national integrity, the State or Government needs to formulate substantial alternative solution soon rather than ceremonial formalistic. Based on eleven offered solutions, both explicitly and implicitly, places the government as the party that decides the success of social violence handling. Our constitution has guaranteed human rights by confessing every Indonesian society rights to get protection from government as stated on Pasal 28G ayat (1) dan (2) Undang-undang Dasar Negara Republik Indonesia Tahun 1945